A comparison of the information seeking behavior of physics and anthropology students at the University of the Philippines - Sison, Jennifer P. (School of Library and Information Studies, University of the Philippines Diliman, 2003)
Differences in information need and information seeking behavior exist within user communities. In order to meet the information needs of the user community, information professionals must first understand the nature of the user community and become familiar with the information seeking habits and practices of the user.